PERANAN JAKSA PENUNTUT UMUM PADA LINGKUP KEJAKSAAN TINGGI PAPUA DALAM PELAKSANAAN DIVERSI PADA PELAKU TINDAK PIDANA ANAK - Nasrullah Nasrullah (LPPM Universitas Ekasakti Padang, 2023)
Child development cannot be separated from the development of community life in the environment where the child is. National development is a process of modernization of globalization which is difficult to avoid in terms of communication, information, and technology, bringing positive and negative consequences. The positive aspects include adding insight and abilities to children in particular. Meanwhile, from the negative side, there are many child cases that occur as a result of the influence of technology, so that many children become victims of crimes, both from rape and obscenity. under the juvenile justice system. Prosecution of juvenile crimes is in conflict with the law because the application of criminal sanctions to juvenile cases in the juvenile justice system is different from the application of sanctions to the adult criminal justice system. Underlying this, this study aims to find out how effective the role of the Public Prosecutor is in implementing diversion against juvenile offenders at the Papua High Court and what factors affect the effectiveness of the role of the Public Prosecutor in implementing diversion against juvenile offenders at the Papua High Court. This type of research is empirical legal research, using primary data and secondary data. The problem approach in this study is the statutory approach (statute approach) by comparing its implementation when a health emergency occurs in Makassar City. The results of this study indicate that the implementation of the criminal act of health quarantine in the Covid-19 health emergency in Makassar City has not proceeded in accordance with the law. This is influenced by law enforcement factors, facilities and infrastructure, and community cultural factors.